PENGARUH KEPEMIMPINAN DAN BUDAYA ORGANISASI TERHADAP KINERJA KARYAWAN PT KAO INDONESIA - Pendi Hasyim; Nuridin (Program Studi Magister Manajemen Universitas Krisnadwipayana, 2020)
This study aims to determine the Effect of Leadership and Organizational Culture on Employee Performance of PT. Kao Indonesia. The population in this study amounted to 300 employees. By using the Slovin formula a sample of 75 employees was obtained. The sampling technique used is simple random sampling. This study uses a quantitative approach, data for this study were obtained through a questionnaire that was filled out by respondents who had been determined. The data analysis method used is a simple and multiple linear regression analysis method. The research results partially show that leadership has a significant effect on employee performance. Organizational culture has a significant effect on employee performance. While simultaneously leadership variables and organizational culture have a positive and significant effect on the performance of employees of PT. Kao Indonesia.